Psychological traumatic events in the recent past and association with diagnosis of cancer - Shah, Fasiha; Shah, Faisal Hyder (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
Emotional stress due to psychological trauma causes immune system dysfunction resulting in high risk of development of cancer. The study aimed to correlation psychological trauma in the past five years of cancer diagnosis. This study was a community based survey including cancer patients diagnosed with different cancers undergoing treatment or follow-up by using snowball sampling and questionnaire based technique. The study was conducted during a period of one year from December 2019 till December 2020. All recruited patients were requested for an interview. The results of the study showed a high rate of major psychological trauma among cancer patients. Sudden death of a close relative with and without trauma of natural disaster were high. The study conclude that risk of cancer development rises with major emotional trauma specially death of a close relative.